Efficacy of chemoprophylaxis and immunoprophylaxis in leprosy prevention: a systematic review and network meta-analysis of randomized controlled trials. (December 2021) - Tawfik, Gehad Mohamed; Biala, Marwa; Yousef, Yomna Mahmoud; Tiwari, Ranjit; Dobs, Monica; Lotfy, Caroline Ibrahim; Farrag, Doha Ahmed; Hue, Anh Tran; Yotsu, Rie Roselyne; Huy, Nguyen Tien
Abstract: Background: Vaccination and single-dose rifampin are the main proven effective intervention types for preventing leprosy among contacts of Mycobacterium leprae endemic areas. Currently, no high-quality evidence is available regarding the best prophylactic intervention. Objectives: Our primary study aim is to detect the most effective prophylactic intervention for the prevention of leprosy. Methods: In May 2019, 12 databases were searched systematically. Updated search terms were developed in March 2020 to complete an updated search. All randomized controlled trials (RCTs) comparing the different types of chemoprophylactic and immunoprophylactic interventions in leprosy prevention were included. Our participants were contacts of patients with leprosy or people residing in leprosy endemic communities. We searched for different types of chemoprophylactic and immunoprophylactic interventions used in leprosy prevention. We used network meta-analysis and meta-analysis. Quality assessment was performed using Cochrane Risk of Bias for included RCTs, in which all included RCTs were rated to be low to moderate risk. We registered our protocol in Prospero with ID CRD42019143207. Results: Among 11 included studies (326 264 patients) from original and updated search terms, eight were eligible for network meta-analysis (NMA) while four were eligible for MA. Findings suggest that Bacillus Calmette–Guérin (BCG) vaccination was the most effective intervention compared to placebo (risk ratios (RRs) 0.49 (0.30, 0.80), p 0.77), followed by combined BCG vaccination and single-dose rifampicin (SDR) with similarly low values (RR 48%, p 0.77). BCG revaccination was the least effective intervention compared to placebo (RR 1.08 (0.36, 3.22), p 0.26). Conclusion: Compared to placebo, the BCG vaccine was the most effective prophylactic intervention. The combination of BCG vaccination + SDR had nearly the same efficacy as BCG vaccination alone, while BCG revaccination was the least effective. Thus, vaccination proved to be a more effective treatment than SDR alone. A well-designed multicenter RCT is warranted to evaluate the safety of these vaccines.